Chiral anomaly, Berry phase, and chiral kinetic theory from worldlines in quantum field theory - Müller, Niklas; Venugopalan, Raju (Physical review, 2018)
In previous work, we outlined a worldline framework that can be used for systematic computations of the chiral magnetic effect (CME) in ultrarelativistic heavy-ion collisions. Towards this end, we first expressed the real part of the fermion determinant in the QCD effective action as a supersymmetric worldline action of spinning, colored, Grassmanian point particles in background gauge fields, with equations of motion that are covariant generalizations of the Bargmann-Michel-Telegdi and Wong equations. The chiral anomaly, in contrast, arises from the phase of the fermion determinant. Remarkably, the latter too can be expressed as a point particle worldline path integral, which can be employed to derive the anomalous axial vector current. We will show here how Berry’s phase can be obtained in a consistent nonrelativistic adiabatic limit of the real part of the fermion determinant. Our work provides a general first principles demonstration that the topology of Berry’s phase is distinct from that of the chiral anomaly confirming prior arguments by Fujikawa in specific contexts. This suggests that chiral kinetic treatments of the CME in heavy-ion collisions that include Berry’s phase alone are incomplete. We outline the elements of a worldline covariant relativistic chiral kinetic theory that captures the physics of how the chiral current is modified by many-body scattering and topological fluctuations.